Unemployment and the Dynamic Effects of Factor Income Taxation - Shouyong Shi; Quan Wen (Queen's University, Department of Economics, 1994)
This paper introduces search unemployment into an intertemporal maximization model with capital accumulation. It characterizes the decentralized search equilibrium, examines the dynamic effects of factor income taxation and calculates the welfare cost of the taxation. Four tax policies are considered: labor income taxation, capital income taxation, the subsidy to job search and the subsidy to hiring. It is found that the dynamic effects and welfare costs of these policies are quite different from the standard model without unemployment. The differences illustrate the importance of the labor market frictions.
Keywords: 330